Plant Growth Promoting Rhizobacteria (PGPR) Concentration and Shade use at Different Levels on Dominant Weed and Green Lettuce (Lactuca Sativa L.) Yield - Santi Kusuma Fajarwati; Fenna Debora; Dewi Ratih Rizki Damaiyanti; Frelyta Ainuz Zahro (Asian Journal of Applied Education (AJAE), 2026)
Horticultural crop cultivation has great potential in Indonesia due to its tropical climate, but there are many obstacles in the process of cultivating horticultural crops. Obstacles in the cultivation of horticultural crops are the emergence of weeds on the land, the absorption of nutrients that are less than optimal, and also the intensity of sunlight, and temperature. This research was conducted on green lettuce (Lactuca sativa L) cultivation land in Kediri Regency, East Java. The research design carried out was Divided Plots Design (RPT) with 2 independent variables, namely the percentage of shading and PGPR concentration. The observation variable is the type of dominant weed and the yield of green lettuce plants, the observation data were then analysed using ANOVA with BNJ 5%. Based on the results of data analysis that has been done, it is known that the weeds that dominate green lettuce cultivation land in 0% and 25% shade treatment are broadleaf weeds, namely purslane and Euphorbia, while the dominant weed in 50% shade treatment is teki. The teki weed that dominates in the 50% shade treatment causes the yield of green lettuce plants, namely the fresh weight of consumption, to be lower than the 25% shade treatment. The second observation variable is the yield of green lettuce plants, in this case the fresh weight of consumption. The largest fresh weight of consumption is in the 25% shade treatment. This is because the 25% shade treatment has an optimal microclimate (temperature, sunlight intensity, and humidity) for green lettuce growth. In addition, the weeds found in the 25% shade treatment were more dominant from the broadleaf weed family which did not have as much allelopathy as the teki tuber..